Identification of the tetracycline resistance gene, tet(O), in Streptococcus pneumoniae. - Widdowson, C A (1996)
Five isolates of Streptococcus pneumoniae resistant to tetracycline but lacking tet(M) were studied. The tetracycline resistance gene, tet(O), was detected for the first time in the pneumococcus. The gene was amplified and sequenced and found to share 99% nucleotide sequence identity and 99, 99, and 98% deduced amino acid sequence identity with the tet(O) resistance genes of Streptococcus mutans, Campylobacter coli, and Campylobacter jejuni, respectively.